Putting the MacBook Air laptop through its paces. - Snell, Jason
The MacBook Air has arrived, a third MacBook model that brings incredibly small size to the MacBook line at a premium price.
Keywords: MacBook (Computer); Laptop computers; Muti-touch.; TrackPad; Optical drive